0619 To Rely or No to Rely: Understanding the Demographics and Polysomnographic Features of False Negative Home Sleep Apnea Testing. (27th May 2020) - Bollu, P; Gurung, P; Mehta, T; Monegro, A; Manjamalai, S; Goyal, M; Thakkar, M; Sahota, P
Abstract: Introduction: The current gold standard for a definitive diagnosis of OSA is an in-center Polysomnography (PSG). Home Sleep Apnea Testing(HSAT) has become an important tool in identifying high-risk populations. One of the limitations of the study is the lack of Electroencephalographic (EEG) data. This prevents the inclusion of Respiratory Effort Related Arousals (RERAs). We attempted to identify the patients whose HSAT showed an REI of less than 5 but are at risk for having sleep apnea based on the presence of airflow and thoraco-abdominal fluctuations. Methods: Patients in this study were those that underwent HSAT from September 2016 till June of 2019. The studies reviewed and interpreted by board certified Sleep Specialists. Studies were done using nox-T3 sleep monitor and Nomad portable Home Sleep Testing type III devices-Both are type 3 Portable Monitors. Only those patients whose REI in their HSAT less than 5 were included in this study. All these patients had multiple airflow fluctuations in their HSAT that raised the suspicion for the presence of RERAs. None of these patients had significant hypoxemia in the HSAT.Airflow fluctuations were defined by the presence of fluctuations in the signal in the airflow channel along with increasing thoracoabdominal channels. Those patients with REI of less than 5 and without airflow fluctuations were excluded from the study. Results: A total of 178 patients were recommended to undergo an in-center polysomnogram. Of those, 92 patients completed their polysomnogram with 59 patients ending up with a diagnosis of sleep apnea while 33 did not suggesting a false negative rate of 64.13%. Of those who were positive, 39 were females while 20 were males. Both groups did not differ significantly. Females had a median BMI of 32.9(28.19 for males), a median ESS of 11(8 in males) and a median RDI of 14.8(13.25). Conclusion: Our study shows that both Home Sleep apnea testing can have a high proportion of false-negative results in patients exhibiting thoraco-abdominal and airflow fluctuations. The interpreting physicians should understand the limitations of the HSAT and should have a low threshold to recommend an in-center polysomnogram. Support: None.